Public Library Services & information Literacy Level for Curriculum Implementation: A Case Study of Language Education Students in Ambrose Ali University - Alufohai, Peace Joan; Alufohai, Odion (Advances in Social Sciences Research Journal, 2020)
The study investigated some of the public library services and information literacy level amongst students. The study was guided by four research questions and one hypothesis. The study adopted the descriptive survey designs. The population for the study consisted of all the 718 English and French language education students while the sample consisted of 168 language education students who patronize the library. The instrument used for data collection is a questionnaire titled Public Library Services and Literary Level Questionnaire (PLSLLQ). The study adopted Descriptive survey design. Statistics of the mean and standard deviation were used to answer the research questions while the Pearson Product Moment Correlation was used to answer the hypothesis. The study revealed amongst others that there is a positive relationship between the services offered in the library and information literacy level, thus revealing that when the services are poor, information literacy will also be poor. Based on the findings, recommendations were made amongst which is that the Nigerian government and stakeholders should ensure adequate funding of public library